Refinement of the criterion for strong localization of electrons on a semiconductor surface - Muratov, Temur T. (Journal of the Belarusian State University. Physics, 2019)
Possibility of strong localization of the two-dimensional electron gas on the surface of the highly doped semiconductor is analyzed. Analytical formula for cross-section of low-energy scattering of surface electrons with take into account Fermi – Dirac’s distribution was obtained. Is noted about substantial feature of the point EF = 0 in quasi two-dimensional electrons systems than in its three-dimensional analogs. On the basis of Ioffe – Regel’s rule and formula obtained for average cross-section of scattering more precise realistic criterion of strong localization was obtained than it which has been obtained in other quoted articles.
Keywords: near-surface layer; natural size effect; Ioffe – Regel’s rule; Thomas – Fermi’s approximation; Fermi – Dirac’s distribution function; criterion of strong localization; cross-section of two-dimensional scattering